Can Whole-Body Vibration Exercises in Different Positions Change Muscular Activity of Upper Limbs? A Randomized Trial - Danielle S Morel; Pedro J Marín; Eloá Moreira-Marconi; Carla F Dionello; Mario Bernardo-Filho (SAGE Publishing, 2018)
The aim of this study was to investigate the acute effects of whole-body vibration exercises (WBVE) in different positions on muscular activity of flexor digitorum superficialis (FD), wrist extensor (ED), and handgrip strength (HG) of healthy men. Fifteen participants have performed 5 test sets each one consisting of HG strength measurement and 1-minute WBVE intervention (frequency: 50 Hz, amplitude: 1.53 mm, synchronous tri-planar oscillating/vibratory platform), that could be control (no exposition to vibration), squat (30 seconds of rest and 30 seconds of WBVE in squat position), or push-up (30 seconds of rest, and 30 seconds of WBVE in push-up position). After testing, participants had 2 minutes of rest and then were encouraged to keep themselves on a pull-up bar for 30 seconds. During all procedures, muscular activity of FD and ED was measured by surface electromyography (EMG). Statistical analysis has revealed that the EMG measured in the FD during the static pull-up bar exercise after SQUAT condition was significantly higher ( P = .004) than the CONTROL and PUSH-UP conditions. Whole-body vibration exercises in squat position increase acutely muscle activation of the FD during isometric exercises of longer duration, while muscle activation of ED and HG strength are not affected by WBVE.